Penerapan Teknologi Sistem Peringatan Dini dalam Upaya Pengurangan Resiko Bencana Hidrometeorologi di Kelurahan Tumbang Tahai: The Application of Early Warning System Technology in Hydrometeorological Disaster Risk Reduction Efforts in Tumbang Tahai Village - Dwinanda, Indah Gumilang; Cassiophea, Lola; Saragih, Osi Karina; Thareq, Subhan Ilham; Permanasuri, Ni Putu Diah Agustin; Kurniawati, Mega (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The high potential of hydrometeorological disasters threatens the livelihoods of the community, especially the people of Tumbang Tahai Village, Socialization of hydrometeorological disaster mitigation aims to increase public awareness of the potential of hydrometeorological disasters that threaten people's lives. Data logger and Android mobile is a system that utilizes ultrasonic waves to determine the height or distance of water from the ground. The method carried out by socialization introduces as well as utilizes the data logger system and Android mobile as a basis for hydrometeorological disaster mitigation. The findings of the hydrometeorological disaster mitigation socialization activities revealed that the community tends not to know about Hydrometeorological disaster mitigation. Training and mentoring are carried out by the community service team to the Tumbang Tahai community through hydrometeorological disaster mitigation based on data loggers and android mobile can provide maximum benefits for the people of Tumbang Tahai Village.